Eco-eficiência baseada nos princípios da produção mais limpa - Agner, Thompson Copperfield Ribas von (2006)
In the present study the concepts of Cleaner Production in the lumber industry was applied. With the intention to contribute for the reduction of raw material, water and energy waste, and aiming at the integration of this industrial sector in the concepts of industrial ecology. The following general objective was elaborated; to develop a proposal for the application of the principles of Cleaner Production in the lumber industry using the concepts of industrial ecology and sustainability. A return was longed in such a way that the organization had an economic and environmental return. It was also observed that companies that possess an environmental management system have and advantage of the cost reduction in operations with the minimization of residues, increasing still more the profitability of the processes. To carry through the study, the productive processes of a lumber mill were mapped and identified the points of initial application of Cleaner Production in the organization. The result were the identification of points where toxic and harmful residues, not only to the natural environment and man, are generated, but also harmful to economy. Another factor was the development of a proposal for the use of Cleaner Production with a sustainability method so that there is an evolution of the industrial systems.